Bioactivity of Novel Pyrazole-Thiazolines Scaffolds against Trypanosoma cruzi: Computational Approaches and 3D Spheroid Model on Drug Discovery for Chagas Disease - Leonardo da Silva Lara; Guilherme Curty Lechuga; Lorraine Martins Rocha Orlando; Byanca Silva Ferreira; Bernardo Araújo Souto; Maurício Silva dos Santos; Mirian Claudia de Souza Pereira (MDPI AG, 2022)
Chagas disease, a century-old disease that mainly affects the impoverished population in Latin America, causes high morbidity and mortality in endemic countries. The available drugs, benznidazole (Bz) and nifurtimox, have limited effectiveness and intense side effects. Drug repurposing, and the development of new chemical entities with potent activity against Trypanosoma cruzi, are a potential source of therapeutic options. The present study describes the biological activity of two new series of pyrazole-thiazoline derivatives, based on optimization of a hit system 5-aminopyrazole-imidazoline previously identified, using structure-activity relationship exploration, and computational and phenotype-based strategies. Promising candidates, 2c, 2e, and 2i derivatives, showed good oral bioavailability and ADMET properties, and low cytotoxicity (CC50 > 100 µM) besides potent activity against trypomastigotes (0.4-2.1 µM) compared to Bz (19.6 ± 2.3 µM). Among them, 2c also stands out, with greater potency against intracellular amastigotes (pIC50 = 5.85). The selected pyrazole-thiazoline derivatives showed good permeability and effectiveness in the 3D spheroids system, but did not sustain parasite clearance in a washout assay. The compounds' mechanism of action is still unknown, since the treatment neither increased reactive oxygen species, nor reduced cysteine protease activity. This new scaffold will be targeted to optimize in order to enhance its biological activity to identify new drug candidates for Chagas disease therapy.